STUDY ON INSPECTION OF THE PUTATIVE HYBRIDS BETWEEN TRACK-LACKING WILD MALE GAUR (BOS GAURUS) AND DOMESTIC FEMALE COW (BOS TAURUS) IN PHUOC BINH NATIONAL PARK, VIETNAM - Duc, Le Hoang; Tung, Pham Thanh; Nam, Nguyen Trung; Ha, Chu Hoang; Tham, Le Xuan; Son, Le Van (Vietnam Journal of Biotechnology, 2018)
Hybridization between wild and domestic bovine occurs widely due to the overlapping of the natural habitat of the wild and human farm animals. Due to the loss of habitat, the number of wild gaur (Bos gaurus) in Vietnam was in serious decline. Since 2009, a male wild gaur (Bos gaurus) has appeared and incorporated with female domestic cows (Bos taurus) in buffer zone Phuoc Binh National Park, on the border with Lam Dong and Ninh Thuan provinces. Then, several calves were born that carried some traits of wild gaur including physical characteristics and behaviors. These calves were supposed to be offspring between wild gaur and domestic cows. In previous study, the karyotypes of putative calves were identified with 2n = 58 and non-homologous chromosome 28 and 29 in these hybrids. In this study, we characterized the putative hybrids between track-lacking Bos gaurus and Bos taurus for breeding and preservation using Cytochrome b analysis, microsatellites and a novel marker growth hormone factor 1 (POU1F1). Cytochrome b analysis indicated the maternal lineage of the putative hybrids, with 100% nucleotide sequence identity. Microsatellite BM861 and sequence of ZFY gene region reveal Bos taurus chromosome Y origin was among the male putative hybrids. Importantly, the analysis of POU1F1 gene sequence on 1 chromosome showed efficacy in determining both Bos gaurus and Bos taurus lineage in the putative hybrids. The karyotyping results were confirmed by molecular analysis and our results provide a feasible way for detecting the putative hybrids between wild and domestic cattle in case of lacking the wild trace.